1985
DOI: 10.1172/jci111775
|View full text |Cite
|
Sign up to set email alerts
|

Role of the endocrine pancreas in the kalemic response to acute metabolic acidosis in conscious dogs.

Abstract: Metabolic acidosis due to organic acids infusion fails to elicit hyperkalemia. Although plasma potassium levels may rise, the increase is smaller than in mineral acid acidosis. The mechanisms responsible for the different effects of organic acid acidosis and mineral acid acidosis remain undefined, although dissimilar hormonal responses by the pancreas may explain the phenomena. To test this hypothesis, beta-hydroxybutyric acid (7 meq/kg) or hydrochloric acid (3 meq/kg) was infused over 30 min into conscious do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
12
0
2

Year Published

1991
1991
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(15 citation statements)
references
References 32 publications
1
12
0
2
Order By: Relevance
“…It was found that the presence of d ‐lactataemia in acidemic calves resulted in significantly lower odds for hyperkalemia but significantly higher odds for the presence of hypokalemia 8. This is in line with the results of experimental studies which reported that a hyperkalemic state can be induced by infusions with inorganic acids such as HCl or ammonium chloride but not if organic acids such as lactic acid, acetic acid or ß‐hydroxybutyrate are infused 24, 25, 26. This disparate effect on K + homeostasis was related to intracellular moving of organic anions which is believed to result in a higher degree of intracellular acidosis and Na + loading and consequently a higher Na + /K + ‐ATPase activity resulting in a net cellular uptake of potassium ions 27.…”
Section: Discussionsupporting
confidence: 63%
“…It was found that the presence of d ‐lactataemia in acidemic calves resulted in significantly lower odds for hyperkalemia but significantly higher odds for the presence of hypokalemia 8. This is in line with the results of experimental studies which reported that a hyperkalemic state can be induced by infusions with inorganic acids such as HCl or ammonium chloride but not if organic acids such as lactic acid, acetic acid or ß‐hydroxybutyrate are infused 24, 25, 26. This disparate effect on K + homeostasis was related to intracellular moving of organic anions which is believed to result in a higher degree of intracellular acidosis and Na + loading and consequently a higher Na + /K + ‐ATPase activity resulting in a net cellular uptake of potassium ions 27.…”
Section: Discussionsupporting
confidence: 63%
“…32 Moreover, differential effects of organic versus hyperchloremic acidosis on insulin and glucagon secretion may contribute to the differing effects of these forms of acidosis on plasma K ϩ as discussed earlier. 33 Although skeletal muscle is the predominant source of intracellular K ϩ content, there is evidence that the effect of organic acid-induced insulin secretion on plasma K ϩ is mediated at least in part by hepatic K ϩ uptake. 33 The interactions of acid-base disturbances with other hormonal systems are at present incompletely defined.…”
Section: Effects Of Acid-base Status On Internal K ؉ Distributionmentioning
confidence: 99%
“…33 Although skeletal muscle is the predominant source of intracellular K ϩ content, there is evidence that the effect of organic acid-induced insulin secretion on plasma K ϩ is mediated at least in part by hepatic K ϩ uptake. 33 The interactions of acid-base disturbances with other hormonal systems are at present incompletely defined.…”
Section: Effects Of Acid-base Status On Internal K ؉ Distributionmentioning
confidence: 99%
“…The authors report that acute NH 4 Cl-induced metabolic acidosis resulted in increased plasma insulin and decreased glucagon levels. Their data are reminiscent of those observed with acute organic acid-induced acidosis (ketoacid infusion) in conscious dogs (which elicited a hypokalemic response) but not those with mineral acidinduced acidosis (which yielded transient hyperkalemia) (10). Thus it would appear that the intravenous administration of 350 ml/h of 5% glucose during the course of acid infusion to the normal volunteers, and not the mineral-acid load itself, was responsible for the reported increase in plasma insulin and decrease in plasma glucagon levels.…”
mentioning
confidence: 68%
“…These derangements in glucoregulation were independent of the activity of the sympathetic nervous system (8). Similar studies were carried out in conscious dogs infused with HCl to discount a confounding effect of pentobarbital anesthesia (10). Acute HCl-induced acidemia caused small and transient but significant increases in plasma glucose levels in hepatic-vein blood but not in arterial blood.…”
mentioning
confidence: 82%